IMPLEMENTASI MANAJEMEN RISIKO DALAM PENINGKATAN EFEKTIVITAS PEMBELAJARAN DI SMKN 4 BANDUNG - Miftahuldzanah, Windy Nurul; Hidayat, Wahyu (ASCENT: Al-Bahjah Journal of Islamic Education Management, 2024)
Risk management in vocational education plays a vital role in the quality of learning. This study examines the implementation of risk management to enhance the effectiveness of learning at SMKN 4 Bandung through a qualitative approach and in-depth analysis methods. Based on a series of observations and interviews, several fundamental challenges in the teaching and learning process were identified, including the diversity of students' comprehension levels, limited practical facilities, and the need for more adaptive teaching strategies. To address these challenges, the school has developed various strategic initiatives, including the creation of standardized operational guidelines, internal teacher training programs, and the preparation of integrated learning tools. Program implementation is monitored through classroom learning supervision, while success is evaluated using academic assessment instruments. However, some issues persist, such as teacher coordination and time management, which require further refinement. Based on these findings, this study proposes strengthening teacher teamwork, improving time management efficiency, and developing sustainable programs to optimize risk management in vocational learning activities.